English and French [NN]N lexical units: A categorial, morphological and semantic comparison. (April 2014) - Arnaud, Pierre J.L.; Renner, Vincent
<x xml:space="preserve">Abstract</x> This article presents a detailed classification of noun-noun nominal lexical units which shows that French and English have the same categories. It then contrasts French subordinative units with their English equivalents, and it appears that French units constitute less prototypical compounds, and their status as morphological or syntactic objects is a matter of debate.